KEBUTUHAN HUMAN CAPITAL DI PROPINSI JAWA TENGAH - Chuzaimah Chuzaimah; Triyono Triyono (Muhammadiyah University Press, 2003)
This research discusses about capital human needs in Central Java Province. The data used involving population number, poor people nutritious index, regional minimum wage, manpower age, income and education with the time range 1995-2001. To analyze capital human needs it. Used Amartye K. Sen formulation model, and to see human resource quality it was used structural similarity approach. The research shows that central Java Province still has serious weakness in capital human needs. This case is shows with capital need and human capital need who has worked whereas; human resource quality is badly influenced by education they have got.